Reinforcer-dependent enhancement of operant responding in opioid-withdrawn rats - Cooper, Ziva D. (2010)
RATIONALE AND OBJECTIVE: Opioid withdrawal increases the reinforcing effectiveness of the µ-opioid agonist remifentanil in rodents. The current study explored the selectivity of this effect by assessing operant behavior maintained by drug and non-drug reinforcers, remifentanil, cocaine, a palatable liquid food, and standard food pellets, as a function of opioid dependence and withdrawal. MATERIALS AND METHODS: Operant responding exhibited by nondependent, morphine-naïve groups was compared with responding exhibited by morphine-dependent and withdrawn groups. Dependence was established using a noncontingent morphine dosing procedure that has been previously verified to maintain dependence while allowing for daily behavioral observation during a withdrawn state. Behavior maintained by remifentanil (0.10–10.0 µg/kg/infusion), cocaine (0.032–1.0 mg/kg/infusion), a palatable liquid food reinforcer (3.2–100.0% Vanilla Ensure(®) and water), or food pellets was assessed in dependent and nondependent groups. RESULTS: Morphine withdrawal enhanced remifentanil self-administration, resulting in an upward and rightward shift of the descending limb of the dose–response curve, and increased operant responding for both food reinforcers. However, opioid withdrawal did not affect cocaine self-administration, nor did it affect responding for water. CONCLUSIONS: Enhanced operant responding observed under opioid-dependent and withdrawn conditions, while selective, is generalized to some nonopioid reinforcers.